Occult Omental Metastasis in Gastric Adenocarcinoma: An Analysis of Incidence, Predictors, and Outcomes - Paul, Negine; Surendran, Suraj; Yacob, Myla; Thenmozhi, Mani; Chandran, Sudhakar; Samarasam, Inian (South Asian Journal of Cancer, 2022)
Introduction Traditionally, the concept of complete omentectomy during gastric resection for cancer was based on lymphatic drainage and the occurrence of occult omental metastasis (OM). However, recent emerging evidence has challenged this concept of complete omentectomy. We, therefore, aim to find the incidence and risk factors of occult OM and also evaluate the outcome of patients with and without such metastasis.Methods This is a single institutional, retrospective study of patients with gastric cancer who underwent curative radical gastrectomy for a period of 3 years (April 1, 2016, to March 31, 2019). A complete omentectomy was performed in all patients and the omentum and nodal stations were dissected in the resected specimen and sent for pathological analysis. Clinical and epidemiological data were collected from the hospital patient database and analysis was done.Results A total of 185 patients have been included in the study, with a mean age of 53.84 years. Twenty of the 185 patients had OM (10.8%). Age, sex, location of the tumor, and neoadjuvant chemotherapy were not statistically significant in predicting OM. However, tumor size and tumor depth were found to have a significant association with OM. The occurrence of OM was more likely to be associated with disease recurrence, especially in the peritoneum. The mean overall survival was 38.15 months (±3.33 SD), whereas patients with OM had lower survival, 23.31 months (±7.79 SD), with a p-value of 0.012.Conclusion OM was not encountered in T1 and T2 gastric cancers and the incidence of OM in T3 and T4 tumors was approximately 12.7%. Therefore, complete omentectomy may be omitted in early T1/T2 tumors. OM was associated with poor prognosis, increased peritoneal recurrence, and decreased overall survival, in spite of a complete omentectomy, and may serve as a prognostic indicator for disease recurrence and overall survival.
Keywords: omentectomy; omental metastasis; gastric cancer; gastrectomy; omental nodes